(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals in sufficient detail the role of nonlinear thinking in the formation of a modern personality, the role of mathematical science in achieving it. Today’s era of digitalization of education is considered important, and it is important to achieve linearity of thinking as one of the main components. From a mathematical point of view, linear reasoning is the process of solving an equation or inequality with a small number of variables in a given sequence. Robots and artificial intelligence systems that have entered human life today are based on non-linear thinking, and they take away and take away routine activities from people. In such conditions, everyone is required to have a sufficient level of creative thinking. But it is impossible to think non-linearly without having creative thinking. In modern conditions, nonlinear thinking is insufficiently studied in the minds of people and in a number of fields of science. It’s even dangerous. In addition, in today’s complex modern world, most events and processes cannot be described by linear models. That is why it is necessary to form non-linear thinking in general education schools and higher educational institutions. In short, in today’s digitalization of education, we cannot guarantee the achievement of educational goals without teaching students to think non-linearly. Therefore, ensuring the achievement of educational goals in advance is one of the basic principles of modern education.